Enhancing indoor air quality and sustainable living in newly constructed apartments: insights from Dubai - Jung, Chuloh; Abdelaziz Mahmoud, Naglaa Sami; Alqassimi, Nahla (Frontiers in Built Environment, 2023)
This research paper examines Indoor Air Quality (IAQ) conditions in newly constructed apartments in Dubai to be more sustainable for residents to have healthier lifestyles. Enhanced airtightness and chemical-laden materials contribute to IAQ pollution in these buildings. The study aims to assess pollutant concentrations and variations based on building height. Measurements were conducted in 12 apartment units using the WHO’s IAQ assessment methodology. Most pollutants were within limits, but TVOC exceeded the Dubai Municipality’s standard, measuring at 2634.4 μg/m³, approximately nine times higher than the standard. HCHO (163.4 μg/m³) and toluene (551.4 μg/m³) were identified as significant pollutants with potential health effects. Analysis of pollutant concentrations based on building height revealed higher TVOC levels in upper areas, with 2,828 μg/m³ in the upper area compared to 2,443 μg/m³ in the lower area, indicating more severe indoor air pollution in Ethylbenzene and styrene also highest in upper areas, with ethylbenzene at 122 μg/m³ and styrene at 82 μg/m³ in the upper area, potentially due to elevated sources. Toluene and xylene concentrations were elevated in the middle area, with toluene at 574 μg/m³ and xylene at 321 μg/m³, likely influenced by materials and occupant activities. Benzene concentrations were consistent across all heights at 2.94 μg/m³, suggesting a common source. HCHO concentrations were relatively consistent but slightly higher in the middle and upper areas, with 171 μg/m³ in both, likely influenced by ventilation and emissions. While average pollutant concentrations met WHO standards, many units exceeded recommended limits, requiring targeted interventions. The study highlights the importance of addressing IAQ concerns and implementing strategies to reduce indoor air pollutants and improve ventilation. These findings contribute to IAQ knowledge in Dubai’s residential buildings, guiding policymakers, architects, and developers in effective policies and guidelines. Further research on seasonal variations and other IAQ factors is recommended for better understanding and long-term monitoring. Prioritizing IAQ in newly constructed apartments is crucial for healthier living in Dubai. The residential building sector can protect residents’ health by implementing appropriate measures while delivering upscale living experiences.